PROFESSIONAL TEACHER EMPOWERMENT: IMPROVEMENT STRATEGIES QUALITY OF MADRASAH EDUCATION IN THE DIGITAL ERA - Sari, Putri Permata (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
In developing superior human resources, the quality of education can be an essential prerequisite. The interaction of technology with education has undoubtedly had a significant impact leading to considerable changes, particularly in learning. There are differences between the learning processes educators and students use in digital environments today and in the past. Where learning occurs, it begins to shift towards a digital learning environment. Therefore, the quality of education must be improved by providing more professional educators. In the digital era, teachers and lecturers can apply various learning tactics, such as making models, generating new ideas, evaluating learning with online media, or preparing professional human resources by using the literature review method with various studies sourced from books, journal articles and other sources that support this paper. The study results the show that improving education quality is an initial priority for all educational institutions, such as madrasas. Thus, several strategies can be offered to increase the quality of education.